2019
DOI: 10.1002/ejic.201801501
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of Formic Acid Catalyzed by Water‐Soluble Ruthenium Complexes: X‐ray Crystal Structure of a Diruthenium Complex

Abstract: Dehydrogenation of formic acid over various Ru‐arene complexes containing N‐donor chelating ligands was investigated in H2O and isolated and characterized several important catalytic intermediate species to elucidate the reaction pathway for formic acid dehydrogenation. Among the studied complexes, Ru‐arene complexes, namely [(η6‐C6H6)Ru(κ2‐NpyNH2‐AmQ)Cl]+ (C‐2), [(η6‐C10H14)Ru(κ2‐NpyNH2‐AmQ)Cl]+ (C‐3) and [(η6‐C6H6)Ru(κ2‐NpyNHMe‐MAmQ)Cl]+ (C‐4) [AmQ = 8‐aminoquinoline and MAmQ = 8‐(N‐methylamino)quinoline] we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 74 publications
1
40
0
Order By: Relevance
“…In 2019, Singh et al reported the catalytic dehydrogenation of formic acid using a water-soluble Ru-arene complex containing N-H moiety [32]. The use of water-soluble catalysts in aqueous solutions allows for environmentally friendly catalysis by avoiding toxic organic solvents.…”
Section: Entry B)mentioning
confidence: 99%
See 2 more Smart Citations
“…In 2019, Singh et al reported the catalytic dehydrogenation of formic acid using a water-soluble Ru-arene complex containing N-H moiety [32]. The use of water-soluble catalysts in aqueous solutions allows for environmentally friendly catalysis by avoiding toxic organic solvents.…”
Section: Entry B)mentioning
confidence: 99%
“…The pathway of formic acid/formaldehyde dehydrogenation using various catalysts. Data obtained from [27][28][29][30][31][32][33][34][35][36]44,45]. Recently, Singh and colleagues reported the ruthenium-catalyzed dehydrogenation of aqueous formaldehyde and paraformaldehyde to produce hydrogen [45].…”
Section: Formaldehydementioning
confidence: 99%
See 1 more Smart Citation
“…Further, to utilize biomass‐derived substrates for the production of hydrogen gas, which is identified as a clean fuel of the future, will not only have a crucial role in diminishing CO 2 emission, but also provide a sustainable route to utilize biomass waste [3–5] . Hydrogen is being produced at an industrial scale by electrolysis of water, [6] methane reforming, [7] enzymatic pathway, [8,9] gasification of biomass waste, [10] steam reforming, [11] aqueous phase reforming [12] and catalytic dehydrogenation of liquid hydrogen carriers [13–19] . However, globally efforts are also being made to explore alternate and effective ways to produce hydrogen gas, and therefore the selection of the sustainable resources and mild reaction conditions for hydrogen production are few of the crucial factors which need specific attention.…”
Section: Introductionmentioning
confidence: 99%
“…Sinjay et al synthesized ruthenium complexes [(η 6 -arene)Ru(κ 2 -L)] n+ (n = 0.1) ([Ru]-1 − [Ru]-9) ligated with pyridine-based ligands and used them to produce hydrogen from formic acid in water. They obtained a very effective and stable catalyst in water, which could be used up to seven times, and they achieved a total turnover frequency (TOF) of 6050 h −1 [41,42].…”
Section: Introductionmentioning
confidence: 99%